A psychological investigation of the extent and implications of labour turnover amongst European employees in a manufacturing industry - Bouwer, B. D. J.(Barend Daniel Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1968.